2017
DOI: 10.4236/ce.2017.814157
|View full text |Cite
|
Sign up to set email alerts
|

The Link between Teaching Methods and Achievement in Math in Computer-Assisted Elementary Schools

Abstract: This study compares the effect of frontal teaching methods on achievement levels in math to those of alternative teaching methods in elementary schools where classroom teaching is reinforced with computer sessions. The study was conducted in two urban, elementary schools in underprivileged areas and involved 479 students in grades 4, 5 and 6 and 18 teachers 9 who used the frontal method and 9 who used the alternative method. Progress was checked while accounting for students' age and level. Significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…This implies that H1 or the direct influence of Exogenous 3 on Endogenous is statistically significant or significant. The results of this study support research conducted by Pujoandika & Sobandi (2021)); Suryani (2021); Rinantanti & Tahir (2019); Hassidov (2017); Ratna et al (2022); Kolovou et al (2021); Francisco & Celon (2020) and Taufan (2022). Pujoandika & Sobandi (2021) stated that teacher performance impacts student learning outcomes because qualified teachers will influence student learning outcomes.…”
Section: The Effect Of Teacher Performance In Learning On Student Lea...supporting
confidence: 88%
See 1 more Smart Citation
“…This implies that H1 or the direct influence of Exogenous 3 on Endogenous is statistically significant or significant. The results of this study support research conducted by Pujoandika & Sobandi (2021)); Suryani (2021); Rinantanti & Tahir (2019); Hassidov (2017); Ratna et al (2022); Kolovou et al (2021); Francisco & Celon (2020) and Taufan (2022). Pujoandika & Sobandi (2021) stated that teacher performance impacts student learning outcomes because qualified teachers will influence student learning outcomes.…”
Section: The Effect Of Teacher Performance In Learning On Student Lea...supporting
confidence: 88%
“…Teacher performance is the teacher's ability to educate, teach, guide, direct, train, assess, and evaluate students in early childhood education through formal, basic, and secondary education (Presiden Republik Indonesia, 2005). According to Pujoandika & Sobandi (2021); Deke (2020); Suryani (2021); Kamil et al (2022); Rinantanti & Tahir (2019); Hassidov (2017); Ratna et al (2022); Kolovou et al (2021);and Francisco & Celon (2020). Taufan (2022) specified his research on English, Mathematics, Science, Filipino, and Araling Panlipunan; the results found that teacher performance influences student academic performance, even though only to a certain extent.…”
Section: Introductionmentioning
confidence: 99%